2002
DOI: 10.1063/1.1463217
|View full text |Cite
|
Sign up to set email alerts
|

Two families of superintegrable and isospectral potentials in two dimensions

Abstract: As an extension of the intertwining operator idea, an algebraic method which provides a link between supersymmetric quantum mechanics and quantum (super)integrability is introduced. By realization of the method in two dimensions, two infinite families of superintegrable and isospectral stationary potentials are generated. The method makes it possible to perform Darboux transformations in such a way that, in addition to the isospectral property, they acquire the superintegrability preserving property. Symmetry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 39 publications
2
55
0
Order By: Relevance
“…The figure on the right correspond to the the points of a q = 3 IUR of so (6). The three sections describe three IUR's of su (3).…”
Section: Eigenstates and Factorizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The figure on the right correspond to the the points of a q = 3 IUR of so (6). The three sections describe three IUR's of su (3).…”
Section: Eigenstates and Factorizationsmentioning
confidence: 99%
“…Let H ℓ and H ℓ ′ be two Hamiltonians related by means of a differential operator X in the following form (6) where the triangular oposite faces correspond to two IUR's of su (3). The figure on the right correspond to the the points of a q = 3 IUR of so (6).…”
Section: Eigenstates and Factorizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the solutions are related to Killing vector fields and isometry group of corresponding space. Our solutions are also closely related to the problem of superintegrability in 2D spaces [1,2,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The Intertwining relationship between differential operators is widely studied in recent years [1,2,3]. This is simply the following relationship between three differential operators H 1 , H 2 and L …”
Section: Introductionmentioning
confidence: 99%